A thermostable laccase from Thermus sp. 2.9 and its potential for delignification of Eucalyptus biomass - Navas, Laura Emilce (2019)
Laccases are multicopper oxidases that are being studied for their potential application in pretreatment strategies of lignocellulosic feedstocks for bioethanol production. Here, we report the expression and characterization of a predicted laccase (LAC_2.9) from the thermophilic bacterial strain Thermus sp. 2.9 and investigate its capacity to delignify lignocellulosic biomass. The purified enzyme displayed a blue color typical of laccases, showed strict copper dependence and retained 80% of its activity after 16 h at 70 °C. At 60 °C, the enzyme oxidized 2,2′-azino-di-(3-ethylbenzthiazoline sulfonate) (ABTS) and 2,6-dimethoxyphenol (DMP) at optimal pH of 5 and 6, respectively. LAC_2.9 had higher substrate specificity (kcat/KM) for DMP with a calculated value that accounts for one of the highest reported for laccases. Further, the enzyme oxidized a phenolic lignin model dimer. The incubation of steam-exploded eucalyptus biomass with LAC_2.9 and 1-hydroxybenzotriazole (HBT) as mediator changed the structural properties of the lignocellulose as evidenced by Fourier transform infrared (FTIR) spectroscopy and thermo-gravimetric analysis (TGA). However, this did not increase the yield of sugars released by enzymatic saccharification. In conclusion, LAC_2.9 is a thermostable laccase with potential application in the delignification of lignocellulosic biomass.